Maimonides as biblical interpreter - Klein-Braslavy, Sara (Emunot., 2011)
Although Maimonides did not write a running commentary on any book of the Bible, biblical exegesis occupies a central place in his writings, particularly in his Guide of the Perplexed. In this book, Sara Klein-Braslavy offers a collection of essays on several key biblical interpretations by Maimonides dealing with the creation of the world; the story of the Garden of Eden; Jacob's dream of the ladder; King Solomon as an esoterist philosopher; and the problem of exoteric and esoteric biblical interpretations in the Guide. Special attention is paid to Maimonides' methods of interpretation and to his esoteric way of writing. Some of the articles in this volume were originally published in Hebrew, and appear here for the first time in English.